Die deutschsprachige Lyrik der Frühen Moderne (1890-1930) - Klaus Wieland (Recherches Germaniques)
The article explains first what we understand by the literary period of classical modernism, constructed by literary criticism, its periodization and its fundamental features and structures on the level of representation and on that of the represented world. By doing that I will point out formal innovations, in other words new literary techniques of representation, as well as new central topics like the city, the social question, the First World War, the crisis of the subject, sexuality and gender relations. I assume that the so-called “Lebensbegriff” is the specific feature of that period, which develops considerably in the course of time. In a second part I will sketch out the four consecutive subsystems of the literary system ‘classical modernism’ – Naturalism, literature around 1900, Expressionism and New Objectivity –, taking into consideration in each case its literary program and lyrical production.